Evaluation of the efficacy of subgingival irrigation in patients with moderate-to-severe chronic periodontitis otherwise indicated for periodontal flap surgeries - Rajni Jain; Rashi Chaturvedi; Nymphea Pandit; Vishakha Grover; Deborah M Lyle; Ashish Jain (Wolters Kluwer Medknow Publications, 2020)
Background: In certain medically and physically compromised; and terminally ill patients, periodontal surgery may not be feasible. They need special attention and assistance for their daily plaque control regimens for the management and maintenance of periodontal conditions. Subgingival irrigation home care devices with antiplaque agents may serve as useful tools in such specific patient populations. Aims: The aim of this study was to evaluate of the efficacy of sub-gingival irrigation in patients with moderate-to-severe chronic periodontitis otherwise indicated for periodontal flap surgeries. Settings and Design: Randomized comparative parallel group interventional clinical trial. Materials and Methods: Forty adults with moderate-to-severe periodontitis, divided inot Group A and B, were subjected to the use of subgingival home irrigations using 0.06% chlorhexidine (CHX) and mouth-rinsing with 15 ml of 0.12% CHX twice daily, respectively after Phase I therapy. Clinical parameters, i.e., gingival index, oral hygiene index simplified, and bleeding on probing scores were assessed at baseline, 2 weeks, 4 weeks, and 12 weeks' postphase I therapy, whereas clinical attachment level (CAL), probing depth (PD), and stain assessment at baseline and 12 weeks following Phase I therapy. Statistical Analysis Used: Statistical Package for Social Sciences (SPSS Inc., Chicago, IL, USA version 15.0 for Windows). Results: A statistically significant difference was seen with the use of 0.06% CHX irrigations in PD (P = 0.004) and CAL (P = 0.002) as compared to the use of mouth rinsing with 0.12% CHX. Similar differences were observed in both intensity (P = 0.014) and area (P = 0.034) of lingual surface staining with greater staining with CHX mouth rinsing. Conclusion: The adjunctive use of subgingival home irrigations using 0.06% CHX has a promising potential to maintain the oral health and results in lesser staining compared to CHX mouth rinsing. The regimen may further obviate the need of periodontal surgery in medically compromised subjects.